Was Accountant/Auditor Behavior Leading op to Enron, Worldcom, and 2007-2008 Market Meltdowns Episodes Ethical? - Dwi Faradiba Siregar; Annisa Rizki Pratiwi; Iskandar Muda (Universitas Muhammadiyah Surabaya, 2024)
The public accounting profession is an accountant who has obtained a license who has the obligation to provide assurance services, including audit services related to historical financial information, review services related to historical financial information, as well as other forms of assurance services related to accounting, management and finance. Apart from having obligations, public accountants also have to obtain compensation, obtain legal protection for providing services determined by SPAP, as well as obtain information, data and other documents related to the provision of services, as regulated by Law of the Republic of Indonesia Number 5 of 2011 concerning Public Accountants. The public accounting profession must uphold ethical values ​​in behavior when carrying out its work. If public accountants ignore professional ethical values, violations and irregularities will occur which can cause scandals, tarnishing the public accounting profession itself, and of course also reducing public trust in public accountants.This research was conducted by conducting a literature study from various studies on ethical behavior and codes of ethics for professional accountants in public accounting. The research method used is a qualitative descriptive method by taking relevant data from literacy studies on research on ethical behavior and codes of ethics for professional accountants in public accounting. The results of this research, enforcing a good code of ethics will help increase public trust in the accounting services provided. In the case of Enron and WorldCom, the behavior of accountants was considered unethical and not in accordance with the applicable code of ethics. In 2007-2008, when the global financial crisis occurred, accountants' behavior, if it complied with the applicable code of ethics, was considered ethical. Meanwhile, if an accountant's behavior violates the applicable code of ethics, it is considered unethical.